The Immunomodulatory Effect and Clinical Efficacy of Daratumumab in a Patient With Cold Agglutinin Disease - Zaninoni, Anna; Giannotta, Juri A.; Gallì, Anna; Artuso, Rosangela; Bianchi, Paola; Malcovati, Luca; Barcellini, Wilma; Fattizzo, Bruno (Frontiers in Immunology, 2021)
Daratumumab is a monoclonal antibody directed against the transmembrane glycoprotein CD38 expressed on plasma cells and lymphoplasmocytes, with a proven efficacy in multiple myeloma. Here we show its clinical efficacy in a patient with cold agglutinin disease (CAD) relapsed after multiple lines of therapy. CAD is caused by cold reactive autoantibodies that induce complement mediated hemolysis and peripheral circulatory symptoms. The disease is also characterized by the presence of monoclonal IgM gammopathy and of a lymphoid bone marrow infiltration that benefits from B-cell targeting therapies (i.e., rituximab) but also from plasma cell directed therapies, such as proteasome inhibitors. In the patient described, we also show that daratumumab therapy influenced the dynamics of several immunoregulatory cytokine levels (IL-6, IL-10, IL-17, IFN-γ, TNF-α, TGF-β) indicating an immunomodulatory effect of the drug beyond plasma cell depletion. In addition, we provide a literature review on the use of daratumumab in autoimmune conditions, including multi-treated and refractory patients with autoimmune hemolytic anemia (both CAD and warm forms), Evans syndrome (association of autoimmune hemolytic anemia and immune thrombocytopenia) and non-hematologic autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis.